The participation dividend of taxation: How citizens in Congo engage more with the state when it tries to tax them - Jonathan Weigel (London School of Economics and Political Science (LSE), Department of International Development, 2020)
This paper provides evidence from a fragile state that citizens demand more of a voice in the government when it tries to tax them. I examine a field experiment randomizing property tax collection across 356 neighborhoods of a large Congolese city. The tax campaign was the first time most citizens had been registered by the state or asked to pay formal taxes. It raised property tax compliance from 0.1%in control to 11.5% in treatment. It also increased political participation by about 5 percentage points (31%): citizens in taxed neighborhoods were more likely to attend townhall meetings hosted by the government or to submit evaluations of its performance. To participate in these ways, the average citizen incurred costs equal to their daily household income, and treated citizens spent 43% more than control. Treated citizens also positively updated about the provincial government, perceiving more revenue, less leakage, and a greater responsibility to provide public goods. The results suggest that broadening the tax base has a 'participation dividend,' a key idea in historical accounts of the emergence of inclusive governance in early modern Europe and a common justification for donor support of tax programs in weak states.
Keywords: H20; P48; D73; 330; Taxation; State capacity; Political participation; Tax bargaining; D.R. Congo; Field experiment